PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KOTA TANGERANG - EKO TRIANTO (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2022)
Abstract: The purpose of this study was to analyze the effect of work discipline, work motivation and work environment on employee performance. The research object selected in this study is Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Tangerang. Data were collected through a questionnaire method that was filled out independently of 80 respondents using a random sampling method. Measurements of related variables were tested using Multiple Linear Regression analysis and using SPSS 25 software. The results of this study prove and conclude that: partially in the t test, the t-count value of work discipline is 0.844, work motivation is 3.166, work environment is 2.869 compared to the value of t-table 1,992. These results indicate that only the t-count of work discipline is less than the t-table, while work motivation and work environment exceed the t-table. These results indicate that partially work discipline does not have a positive and significant effect on employee performance, partially work motivation has a positive and significant effect on employee performance and partially the work environment has a positive and significant effect on employee performance. Simultaneously in the F test, the calculated F value of the model is 15.915 with a probability value of Sig. 0.000, the F-table value is 2.72. Because the value of F-count greather than F-table (15.915 greather than 2.72) and the value of Sig. less than 0.05 (0.000 less than 0.05). This shows that work discipline, work motivation and work environment simultaneously have a positive and significant effect on employee performance. The results of the analysis of the coefficient of determination show that work discipline, work motivation and work environment have an influence of 36.2% on employee performance and the remaining 63.8% is explained by other variables not included in this study. Keywords: Work Discipline, Work Motivation, Work Environment and Employee Performance